1992
DOI: 10.1177/104063879200400406
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical Infectious Bursal Disease in an Integrated Broiler Production Operation

Abstract: Abstract. A field study was designed to determine the prevalence of subclinical infectious bursal disease (IBD) in broiler chickens from a commercial poultry company. Bursae of Fabricius (BF) from two vaccinated and three nonvaccinated broiler flocks were evaluated histologically, and antibody profiles of these broiler and matched parent breeder flocks were established. Lesions of IBD, including lymphoid necrosis, stromal edema, and infiltrates of heterophils and macrophages, were first detected in BF at 24 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 14 publications
0
7
0
1
Order By: Relevance
“…In case of no vaccination, morbidity in the flock is 90% (Cook et al, 1999;Cavanagh, 2003). 2 Although Homer et al (1992) found a prevalence rate of 13.3%, the present study assumed that birds have been vaccinated against infectious bursal disease (IBD), indicating that IBD does not occur on the farm. Cavanagh (2003) suggested that vaccination against IBD provides 100% protection.…”
Section: Sensitivity Analysismentioning
confidence: 69%
“…In case of no vaccination, morbidity in the flock is 90% (Cook et al, 1999;Cavanagh, 2003). 2 Although Homer et al (1992) found a prevalence rate of 13.3%, the present study assumed that birds have been vaccinated against infectious bursal disease (IBD), indicating that IBD does not occur on the farm. Cavanagh (2003) suggested that vaccination against IBD provides 100% protection.…”
Section: Sensitivity Analysismentioning
confidence: 69%
“…1994). Maternal antibodies protected chicken against clinical haemorrhagic enteritis (Fadly & Nazerian 1989), against avian leukosis virus (Fadly & Smith 1991) and against infectious bursal disease (Komine 1989;Homer et al . 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Infectious bursal disease (IBD) is an acute, highly contagious, immunosuppressive and economically important poultry disease caused by Birnaviridae RNA virus (Cosgrove, 1962;Lukert and Saif, 2003;Islam, 2005;Okwor et al, 2011). The disease damage the humoral immunity producing lymphoid organ Bursa of Fabricius and result in immuno-suppression and increase susceptibility of poultry to opportunistic secondary infection such as Marek's disease and Newcastle disease (Faragher et al, 1974;Homer et al, 1992;Khan et al, 2011;Mahgoub, 2012). Broiler bird aged between 21-30 days are most susceptible to IBD infection (Mor et al, 2010).…”
Section: Introductionmentioning
confidence: 99%